Optimization of the cell microenvironment in a dual magnetic-pH-sensitive hydrogel-based scaffold by multiphysics modeling - Liu, Qimin (2020)
A dual magnetic-pH-sensitive hydrogel-based scaffold was studied for optimization of a cell microenvironment by scaffold mechanical deformation and its biochemical response. In particular, the positions of the seeding cells and the concentration of potassium (K+) within the scaffold were optimized by a multieffect-coupling magnetic-pH-stimuli (MECmpH) model based on (i) the threshold of the mechanical force required for a mechanotransduction effect at the cellular level, and (ii) the common biological requirement for cell growth. In this model, the physicochemical mechanisms of a magnetic hydrogel were characterized using magneto-chemo-electro-mechanical coupled effects, including hydrogel magnetization, diffusion of the solvent and ions, ionic polarization, and nonlinear deformation. After validation of the model with experimental data, it was found that a higher pH and current intensity at the electromagnet and a shorter hydrogel-magnet distance contribute to larger scaffold deformation and thus a stronger mechanical force on the cells. Moreover, the cell seeding positions within the magnetic scaffold were optimized for improved cell culture through controlled current intensity in the electromagnet. Furthermore, the physiological concentration of K+ was also optimized by the initial fixed charge density within the scaffold. We concluded that this optimized magnetic scaffold via the MECmpH model may provide an appropriate microenvironment for efficient cell growth.